A BIBLIOMETRIC ANALYSIS OF ZAKAT LITERATURE FROM 1964 TO 2021 - Supriani, Indri; Iswati, Sri; Bella, Firsty Izzata; T, Yunice Karina (Universitas Muhammadiyah Surakarta, 2022)
This research provides a comprehensive historical and present development of zakat literature through bibliometrics analysis extracted from the Scopus database using Publish or Perish (PoP), RStudio, and VOSviewer. This study confirms that the literature on zakat has significantly increased during the last fifty years (1964–2021). This research identified that zakat literature had been comprehensively discussed by researchers across the nation from six aspects of research, namely the governance of zakat institutions; zakat as a poverty eradication tool; zakat compliance in an Islamic perspective; zakat as a social security scheme; the intention to pay zakat; and the distribution of zakat. This study confirms that Malaysian scholars and educational institutions have demonstrated a strong research commitment to the theme of zakat.